The Effect of the Big Book Media-Based Discovery Learning Model on Class III Students’ Learning Outcomes on Theme 7 Technological Development at Agia Sophia Private Elementary School - Ita Tarigan, Rosenda; Janson Silaban, Patri; Wulan Sari HS, Dyan; Remigius Abi, Antonius; Pinem, Irmina (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This study seeks the effect of the discovery learning model based on Big Book media on student learning outcomes on theme 7 Technological developments in class III of Agia Sophia Private Elementary School in the academic year 2023/2024. This research used quantitative methods. The sampling technique used purposive sampling and the sample used was 30 students in class III. The research results show that student learning outcomes using the Discovery Learning model based on Big Book media are in the excellent category with an average of 80.3 with a correlation test result of 0.846, which means rcount is 0.846 ≥ rtable is 0.367, so Ha is accepted. Therefore, there is a strong effect between the Discovery Learning model based on Big Book media and the student learning outcomes in theme 7 Technological developments in class III of Agia Sophia Private Elementary School in the academic year 2023/2024. It can be seen from the results of the T-test research where tcount 8.403 ≥ ttable 2.048 so Ha is accepted. This shows a significant positive effect from the Discovery Learning based on Big Book media on student learning outcomes in theme 7 Technological developments in class III of Agia Sophia Private Elementary School in the academic year 2023/2024.